Developing Powerpoint Interactive Media to Teach Speaking Skill For 7th Grade Students - Ningtyas, Aprilia Syafna; Mubarok, Tyas Alhim; Makrifah, Istina Atul (IKIP Siliwangi, 2025)
This research and development aims to describe the process and results of the development of Power Point Interactive media for teaching speaking on greeting, leave taking, and introduction materials. The subjects of the study were 30 students of 7th grade MTs Sunan Kalijogo. The development procedure refers to the Borg and Gall model. The information collection techniques in the preliminary study were interview and questionnaire. Meanwhile, to determine the feasibility of the Interactive Power Point product, the researcher used a questionnaire instrument given to material expert and media expert. Then, students were given a pre-test and post-test. In addition, the distribution of student response questionnaires to determine the level of student satisfaction with the media. According to the assessment of material expert, a score of 97.5% was obtained with a very valid category. From media experts, a score of 100% was obtained with a very valid category. Furthermore, the results of the pre-test and post-test with the calculation of the N-Gain formula obtained results of 0.8 with high qualifications. The student response questionnaire also obtained a score of 94% with a very feasible category. The last, Power Point Interactive was declared very suitable for use in teaching speaking skill.